Efektivitas Pendekatan Modifikasi Perilaku dengan Teknik Fading dan Token Economy dalam Meningkatkan Kosakata Siswa Tuna Rungu Prelingual Profound - Stella Bunga Parmawati; Wuri Prasetyawati; Rose Mini A. Prianto (Psibernetika, 2015)
A profound hearing impairment that happens before the development of language causes several problems for the individual’s academic process and daily communication. Providing an intervention to increase deaf students’ vocabulary as the foundation of their language development is essential. This research was aimed to examine the effectiveness of behavior modification approach using fading and token economy techniques to increase the vocabulary of a student with prelingual profound deafness. The intervention program was adapted from Morris (1985) to teach names of objects and activities. The subject was given three steps of prompt fading and a token every time he succeeded in writing the correct word. Research was conducted on a male prelingual profound deaf student studying at an inclusive primary school who has an average level of non verbal intelligence. Using a single-subject-ABA-single factor research design, the increase in vocabulary is determined by comparing pre-test and post-test. Results indicating that a behavior modification approach using fading and token economy techniques is effective to increase the vocabulary of a student with prelingual profound deafness. The subject was able to understand and produce 87,5% of the eight objects’ names and 100% of the eight activities’ names given.  Keywords: behavior modification, fading, token economy, vocabulary, deaf